The RELATIONSHIP OF MENSTRUAL PATTERNS WITH HEMOGLOBIN LEVELS IN ADOLESCENT WOMEN IN BONDOWOSO STATE 3 HIGH SCHOOL - Zainiah, Putri Nur; Hidayati, Ainul (Journal of Nursing Periodic, 2025)
Introduction: Anemia in adolescents can cause decreased concentration in learning, often feel tired, easily sleepy and decreased endurance. Hemoglobin levels are influenced by the adequacy of iron in the body and protein content. Low protein consumption in daily food so that it does not meet the body's nutritional adequacy. Protein is a component of hemoglobin and plays an important role in transporting oxygen and nutrients. One of the triggers for anemia is an abnormal menstrual cycle. Losing a lot of blood during menstruation is thought to cause anemia (Pada et al., 2024). Objective: To determine the relationship between menstrual patterns and hemoglobin levels in female adolescents at SMA Negeri 3 Bondowoso. Method: The type of research is a correlational analytical study with a cross-sectional design. The population in this study were all female adolescents at SMA Negeri 3 Bondowoso, totaling 159 female students. The number of samples was obtained from the Slovin formula, namely 61 respondents, using the nonprobability sampling method with simple random sampling. Univariate analysis with frequency distribution, and bivariate analysis using the chi square test. The instrument in this study adopted the menstrual pattern questionnaire from Sunirah (2024) and the Easy Touch tool on hemoglobin levels. Results: Most respondents had normal menstrual patterns as many as 36 (59.0%), almost half had abnormal menstrual patterns as many as 25 (41.0%), and most respondents had normal hemoglobin levels as many as 38 (62.3%), almost half of the respondents had low hemoglobin levels as many as 23 (37.7%). From the chi-Square analysis, it was obtained p value (0.001) <α (0.05) meaning Ha was accepted, namely there was a positive relationship with a contingency coefficient value of 0.412 which means a moderate relationship. Conclusion: There is a relationship between menstrual patterns and hemoglobin levels in female adolescents at SMA Negeri 3 Bondowoso. Suggestion: It is hoped that female adolescents will be willing to consume blood-boosting tablets during menstruation, in order to avoid anemia which can interfere with their concentration in learning. And consume foods that can prevent anemia such as beef, liver, nuts and vegetables.